2011
DOI: 10.1177/2156759x1101500101
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Psychometric Properties of School Counselor Self-Advocacy Questionnaire

Abstract: This article reports on the development and the exploration of the underlying psychometric properties of the School Counselor Self-Advocacy Questionnaire, a measure of skills school counselors can use to advocate for their roles and programs. An exploratory factor analysis (N = 188) suggested a unidimensional model, and a confirmatory factor analysis indicated the overall model robustly explains the data, accounting for 80% of the variance. Cronbach's alpha reliability estimates ranged from .84 to .87 for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The survey consisted of 20 items, broken down by (a) demographic items ( n = 7 items), (b) the School Counselor Self-Advocacy Questionnaire (SCSAQ; Clemons, Shipp, & Kimbel, 2011; n = 9 items), and (c) open-ended items ( n = 4 items). Clemons, Shipp, and Kimbel (2011) created the SCSAQ to assess the skills that school counselors use related to role promotion, focusing on school-level advocacy (i.e., microsystem) between principals and counselors. The SCSAQ also helps to identify school counselors’ strengths and weaknesses related to how they engage in professional advocacy at the school level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey consisted of 20 items, broken down by (a) demographic items ( n = 7 items), (b) the School Counselor Self-Advocacy Questionnaire (SCSAQ; Clemons, Shipp, & Kimbel, 2011; n = 9 items), and (c) open-ended items ( n = 4 items). Clemons, Shipp, and Kimbel (2011) created the SCSAQ to assess the skills that school counselors use related to role promotion, focusing on school-level advocacy (i.e., microsystem) between principals and counselors. The SCSAQ also helps to identify school counselors’ strengths and weaknesses related to how they engage in professional advocacy at the school level.…”
Section: Methodsmentioning
confidence: 99%
“…The SCSAQ uses Likert-type scale responses, with participants responding to a 4-point scale from 1 ( strongly disagree ) to 4 ( strongly agree ). We selected this instrument because it has been shown to have high interitem reliability (α = .84) and it is one of the only instruments designed specifically to measure professional advocacy in school counseling (Clemons et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…To that end, scholars have developed general advocacy instruments for use with school counselors. For instance, Clemens et al (2011) created a School Counselor Self-Advocacy Questionnaire and an exploratory and confirmatory factor analysis of responses from 188 school counselors identified a single factor that the authors identified as Advocacy. Haskins and Singh (2016) wrote a School Counseling Advocacy Assessment; their exploratory factor analysis of 332 participants' responses identified five factors: (a) Collaboration with School Groups, (b) Political and Social Actions to Change the System, (c) Individual Student Empowerment, (d) Actions to Reduce Achievement Barriers, and (e) Media Advocacy.…”
mentioning
confidence: 99%
“…First, fewer reports about advocacy outcomes at the exo- and macrosystem levels may be attributed to the lack of methods available to assess school counselors’ engagement at these levels. For example, one of the only published school counselor advocacy scales, the School Counselor Self Advocacy Questionnaire (SCSAQ; Clemens et al, 2011) focuses solely on microsystem advocacy and is designed to provide insights regarding advocacy behaviors within a school counselor’s building. Second, engagement in advocacy behaviors may be affected by school counselor-specific factors including self-efficacy regarding advocacy behaviors (Perry et al, 2020), training in advocacy behaviors (Havlik, Malott et al, 2019), and fear or apprehension about the risks involved in advocating both within and outside their school settings (Beck & Lane, 2019; Havlik, DeRosato, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%